Comparative transcriptome profiling and weighted gene co-expression network analysis to identify core genes in maize (Zea mays L.) silks infected by multiple fungi - Kumar, Amrendra; Kanak, Kanak Raj; Arunachalam, Annamalai; Dass, Regina Sharmila; Lakshmi, P. T. V. (Frontiers in Plant Science, 2022)
Maize (Zea mays L.) is the third most popular Poaceae crop after wheat and rice, used in feed and pharmaceutical sectors. The maize silk contains bioactive components explored by traditional Chinese herbal medicine for various pharmacological activities. However, Fusarium graminearum, Fusarium verticillioides, Trichoderma atroviride, and Ustilago maydis can infect the maize, produce mycotoxins, hamper the quantity and quality of silk production and further harm the primary consumer’s health. However, the defense mechanism is not fully understood in multiple fungal infections in the silk of Z. mays. In this study, we applied bioinformatics approaches to use the publicly available transcriptome data of Z. mays silk affected by multiple fungal flora to identify core genes involved in combatting disease response. Differentially Expressed Genes (DEGs) were identified among intra and inter-transcriptome data sets of control versus infected Z. mays silks. Further comparison between up- and down-regulated genes within the control of datasets, 4519 up-regulated and 5125 down-regulated genes were found. The DEGs have been compared with genes in modules of WGCNA to relevant specific traits towards identifying core genes. The expression pattern of transcription factors (TF), carbohydrate-active enzymes (CAZyme), and resistance (R) genes were analysed. The present investigation is supportive of our findings that the gene ontology, immunity stimulus, and resistance genes are upregulated, but physical and metabolic processes such as cell wall organizations and pectin synthesis were down-regulated respectively. Our results are indicative that terpene synthase TPS6 and TPS11 are involved in the defense mechanism against fungal infections in maize silk.